2020
DOI: 10.1038/s41467-019-14156-4
|View full text |Cite
|
Sign up to set email alerts
|

A robust and efficient method for Mendelian randomization with hundreds of genetic variants

Abstract: Mendelian randomization (MR) is an epidemiological technique that uses genetic variants to distinguish correlation from causation in observational data. The reliability of a MR investigation depends on the validity of the genetic variants as instrumental variables (IVs). We develop the contamination mixture method, a method for MR with two modalities. First, it identifies groups of genetic variants with similar causal estimates, which may represent distinct mechanisms by which the risk factor influences the ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
397
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 452 publications
(403 citation statements)
references
References 57 publications
5
397
1
Order By: Relevance
“…The contamination mixture method assumes that only some of the genetic variants are valid IVs (Burgess, Foley, Allara, Staley, & Howson, 2020). We construct a likelihood function from the ratio estimates.…”
Section: Methodsmentioning
confidence: 99%
“…The contamination mixture method assumes that only some of the genetic variants are valid IVs (Burgess, Foley, Allara, Staley, & Howson, 2020). We construct a likelihood function from the ratio estimates.…”
Section: Methodsmentioning
confidence: 99%
“…As sensitivity analyses, we used the weighted median, MR-Egger, MR Pleiotropy RESidual Sum and Outlier (MR-PRESSO) and contamination mixture methods. 23,[27][28][29] In an additional sensitivity analysis, we excluded selfreported cancer in UK Biobank. We further conducted a sensitivity analysis using the SNP in the IGF1 gene (rs11111274), which was strongly associated with IGF-1 levels (7.59 × 10 −175 ), as genetic instrument.…”
Section: Introductionmentioning
confidence: 99%
“…If data on genetic associations with multiple traits were used to cluster variants, then the clusters might be more precisely defined, but it would not be possible to determine which traits were driving the division into clusters without further analysis. We have previously demonstrated that a group of variants having similar causal estimates for the effect of HDL-cholesterol on CAD risk also had a distinct pattern of associations with blood cell traits, although without using a formal clustering method [30]. The associations with blood cell traits suggested a causal pathway relating to platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%